URGENSI PENGATURAN MENGENAI LARANGAN DISKRIMINASI USIA DALAM PROSES REKRUTMEN DI INDONESIA - Simanullang, R. A Hotmartua; Sitanggang, Tio Theresia; Ferencia, Viony; Tambunan, Johannes Leonard; Wibowo, Bagus Sultan; Afnila; Yusrin (Legislatif, 2024)
Age discrimination in recruitment processes remains a significant issue in Indonesia, where many companies set age limits for job seekers. This practice is allowed under Article 35 of Law 13/2003, which grants employers the freedom to establish their own job requirements, resulting in injustice and limiting job opportunities for older individuals. This study uses a normative legal research approach, analyzing age discrimination regulations in various countries, as well as an analysis of Constitutional Court Decision Number 35/PUU-XXII/2024 and a conceptual approach to develop an anti-discrimination legal framework. The results show that age restrictions in recruitment are discriminatory, failing to provide legal justice, certainty, and benefits for job seekers. Legal studies of other countries regulations reveal that countries like the Philippines and Germany have explicit laws prohibiting age-based discrimination in employment. Although the Constitutional Court rejected the claim that Article 35 of Law 13/2003 is unconstitutional, a dissenting opinion from the judge highlighted the subjectivity of age-based requirements. This underscores the need for legislative reforms in Indonesia to establish clear anti-age discrimination laws, ensuring fairness and equal opportunities in recruitment processes. Therefore, it is crucial to implement policies that focus on job seekers competencies, experience, and skills, without being influenced by age.